2015
DOI: 10.1002/ar.23268
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of the Inner Ear at Different Stages of Normal Human Development

Abstract: This study examined the external morphology and morphometry of the human embryonic inner ear membranous labyrinth and documented its three-dimensional position in the developing embryo using phasecontrast X-ray computed tomography and magnetic resonance imaging. A total of 27 samples between Carnegie stage (CS) 17 and the postembryonic phase during trimester 1 (approximately 6-10 weeks after fertilization) were included. The otic vesicle elongated along the dorsoventral axis and differentiated into the end lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Thayyil et al [14] was able to achieve full body datasets with a reasonable resolution of 200-μm isotropic voxel size in 70 min. This is considerably shorter than other groups that needed 20 to 78 h to visualize the development of the inner ear with an isotropic voxel size of 35 to 55 μm [42,43]. This is due to the fact that reduction in voxel size by a factor 2 in 3-dimension results in a reduction in signal by a factor 2 × 2 × 2 = 8.…”
Section: Imagingmentioning
confidence: 94%
“…Thayyil et al [14] was able to achieve full body datasets with a reasonable resolution of 200-μm isotropic voxel size in 70 min. This is considerably shorter than other groups that needed 20 to 78 h to visualize the development of the inner ear with an isotropic voxel size of 35 to 55 μm [42,43]. This is due to the fact that reduction in voxel size by a factor 2 in 3-dimension results in a reduction in signal by a factor 2 × 2 × 2 = 8.…”
Section: Imagingmentioning
confidence: 94%
“…A greater understanding of the development of the perilymphatic space may facilitate insight into the mechanism underlying such diseases. In our recent study, we observed the formation of a membranous labyrinth during the embryonic and early fetal period (Toyoda et al, 2015). The membranous labyrinth was already differentiated into three sections, that is, the CD, SDs, and vestibule, in samples representing the end of the embryonic stage, which suggest that the membranous labyrinth increases in size during the fetal period.…”
mentioning
confidence: 84%
“… [1] Nakashima et al , [2] Kobayashi et al , [3–5] Shiraishi et al , [6] Shiraishi et al , [7] Taketani et al , [8] Yoshida et al, in press, [9] Takakuwa et al, , [10] Mehemed et al, , [11] Kishimoto et al, , [12,13] Toyoda et al, , [14] Kagurasho et al, , [15] Ozeki‐Sato et al, a, [16] Ozeki‐Sato et al, , [17] Osaka et al, , [18] Ueno et al, , [19] Kaigai et al, . [20] Nako et al, , [21] Ueda et al, , [22,23] Hirose et al, , 2016, [24] Hamabe et al, , [25] Kanahashi et al, , [26] Endo et al, , [27] Takakuwa et al, , [28] Shiraishi et al, .…”
Section: Methodsmentioning
confidence: 99%